Evaluation of water quality due to the use of intensive fertilizer on farmer level in the upstream of Bedadung Jember Watershed, East Java, Indonesia - Fariz Kustiawan Alfarisy; Idah Andriyani; Cahyoadi Bowo (Brawijaya University, 2020)
Upstream cultivation activities by use intensive fertilization have an impact on water quality degradation. Accumulation within several decades will cause damage to the hydrological conditions the watershed. Residual substances and heavy metals due to intensive fertilization will affect the biotic and abiotic components of the watershed ecosystem. Water in Indonesia is divided into several classes, namely class I, II, III and IV. Every class has a quality standard according to its designation class. This study aimed at evaluating the status of water quality based on physical and chemical parameters in the upstream area (rainfall catchment). Water sampling was carried out at three points, namely water sources (in), locations of aquaculture activities (irrigation), and rivers (out). Chemical parameter results showed that DO was 7.16 mgO2/ L in the river (out), BOD was 7.84 mg/L in irrigation, COD in the river was 25,50 mg/L, the irrigation point nitrate was 6.75 mg/L, and pH average was 6.80 almost at each sample point. As for the physical parameters consisting of colour, smell, and temperature. The physical parameters based on Government Regulation No. 82/2001 were still in accordance with the specified quality standards. Management through monitoring river water quality requires an integrated model as an effort to conserve water resources. Result Rapid Rural Appraisal in the upstream area of the Bedadung Jember watershed showed that the role of institutions at the farm level was less than optimal. Communication between farmers level, agricultural extension workers, and several stakeholders was not good. Meanwhile, the participation of the community and several stakeholders had an important role as users of natural resources in conservation.